Persistently high glucose levels in young children with type 1 diabetes. Issue 2 (11th December 2014) - Tansey, M; Beck, R; Ruedy, K; Tamborlane, W; Cheng, P; Kollman, C; Fox, L; Weinzimer, S; Mauras, N; White, NH; Tsalikian, E; ,
Abstract : Objectives: The aim of the study was to characterize glucose levels and variability in young children with type 1 diabetes (T1D). Methods: A total of 144 children of 4–10 yr old diagnosed with T1D prior to age 8 were recruited at five DirecNet centers. Participants used a continuous glucose monitor (CGM) every 3 months during an 18‐month study. Among the 144 participants, 135 (mean age 7.0 yr, 47% female) had a minimum of 48 h of CGM data at more than five of seven visits and were included in analyses. CGM metrics for different times of day were analyzed. Results: Mean hemoglobin A1c (HbA1c) at the beginning and end of the study was 7.9% (63 mmol/mol). Fifty percent of participants had glucose levels >180 mg/dL (10.0 mmol/L) for >12 h/d and >250 mg/dL (13.9 mmol/L) for >6 h/d. Median time <70 mg/dL (3.9 mmol/L) was 66 min/d and <60 mg/dL (3.3 mmol/L) was 39 min/d. Mean amplitude of glycemic excursions (MAGE) was lowest overnight (00:00–06:00 hours). The percent of CGM values 71–180 mg/dL (3.9–10.0 mmol/L) and the overall mean glucose correlated with HbA1c at all visits. There were no differences in CGM mean glucose or coefficient of variation between the age groups of 4 and <6, 6 and <8, and 8 and <10. Conclusions: Suboptimal glycemic control is common in young children with T1D as reflected by glucose levels in the hyperglycemic range for much of the day. New approaches to reduce postprandial glycemic excursions and increase time in the normal range for glucose in young children with T1D are critically needed. Glycemic targets in this age range should be revisited.